AAV manufacturing for clinical use: Insights on current challenges from the upstream process perspective. (December 2021) - Dobrowsky, Terrence; Gianni, Davide; Pieracci, John; Suh, Junghae
Abstract: As gene therapy is experiencing a second wave of interest, recombinant adeno-associated virus (rAAV) has rapidly emerged as one of the most attractive viral transfer tools, thanks to its favorable safety profile and long-term transgene expression. The recent approval of rAAV molecules for the treatment of congenital amaurosis and spinal muscular atrophy has been paving the road for the development of several rAAV-based therapeutics targeting a continuously increasing range of indications. To support this rapid growth, the field is in high demand for robust, scalable and economically viable manufacturing processes. This review will provide an overview of the most common platforms currently adopted at the manufacturing level for rAAV production, focusing on the challenges and bottlenecks experienced in the upstream process.